Perancangan Sistem PPIC Karoseri Minibus di PT. X - Jonathan Suherman Handoyo; Tanti Octavia (Jurnal Titra, 2022)
PT. X is a company engaged in the body body sector. The company is growing, marked by the increasing number of orders, production volume, and the number of types of products. The absence of an unplanned production schedule and raw materials caused this company to be late in delivery and suffered indirect material losses. Due to the absence of a PPIC system in the company, this causes inaccurate production times so that the time given to customers is often missed. Therefore, this company increasingly needs planning for its production and inventory. In designing the PPIC system, so that in the future the production process can run according to the plan and the completion time will be as promised to the customer. the method used is the method of forecasting and production planning, the preparation of the master production schedule, and the raw material requirements as well as the schedule for ordering the required raw materials.